'All the People in the Ring Together': Hemingway, Performance, and the Politics of the Corrida. Issue 1 (March 2016) - Barnes, David
Abstract : Ernest Hemingway's association with the Spanish bullfight ( corrida ) has become a familiar, almost clichéd, aspect of his personal mythology. However, the complexities of the cultural and political discourses around the corrida in Hemingway's writing have not been fully explored. This essay reads Hemingway's engagement with bullfighting as part of a wider interest in the performance or ritual mediation of national identity in his work. It argues that Hemingway's interest in the essence of the bullfight can be linked to the articulations of 'Spanishness' propagated by the Primo De Rivera dictatorship in the mid-1920s. It sees Hemingway's interest in the bullfight as part of a broader struggle within American modernism to articulate national or communal visions of society ('all the people in the ring together') in the two decades following the First World War.